2021
DOI: 10.1111/acel.13501
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric C‐reactive protein via endothelial CD31 for neurovascular inflammation in an ApoE genotype‐dependent pattern: A risk factor for Alzheimer’s disease?

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 67 publications
1
37
0
Order By: Relevance
“…Other studies suggest a pathological role for mCRP in atherosclerosis, thrombosis, angiogenesis, and cerebrovascular pathologies ( 96 , 97 ). mCRP antigen has been found in brain tissues associated with damaged micro vessels and in human and mouse brains involved with neuroinflammation ( 98 100 ). Since mCRP forms from pCRP, drugs that inhibit the in situ formation of mCRP from pCRP could have therapeutic value in treating both systemic and cerebral inflammatory diseases ( 3 , 101 ).…”
Section: Clinical Relevance Of C-reactive Protein-lipoprotein Interac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies suggest a pathological role for mCRP in atherosclerosis, thrombosis, angiogenesis, and cerebrovascular pathologies ( 96 , 97 ). mCRP antigen has been found in brain tissues associated with damaged micro vessels and in human and mouse brains involved with neuroinflammation ( 98 100 ). Since mCRP forms from pCRP, drugs that inhibit the in situ formation of mCRP from pCRP could have therapeutic value in treating both systemic and cerebral inflammatory diseases ( 3 , 101 ).…”
Section: Clinical Relevance Of C-reactive Protein-lipoprotein Interac...mentioning
confidence: 99%
“…A relationship between apo E4 and plasma CRP levels relevant to the development of Alzheimer’s disease has been reported ( 104 ). Furthermore, the mCRP isoform bound to endothelial cell CD31 (a receptor mediating platelet and leukocyte binding and transcytosis), influencing apo E4-related responses in the development of Alzheimer’s disease ( 100 ).…”
Section: Clinical Relevance Of C-reactive Protein-lipoprotein Interac...mentioning
confidence: 99%
“…Indeed, our recent research shows that peripheral intraperitoneal injection of mCRP into APOE knock‐in mice induced significant neuroinflammation of astrocytes and microglia in the brain of APOE ε4 mice. 41 On the other hand, the receptor(s) for mCRP's activities in neurons is unknown. However, it is shown that CRP can bind to phosphocholine in cell membrane and bind to FcgammaRI and FcgammaRIIa in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, further investigations have confirmed the ability of mCRP following hippocampal injection in mice, to induce behavioral and memory/cognitive deficits (which was protected against following co-injection of a specific antibody against mCRP) whilst co-localizing with both phosphorylated Tau (p-Tau) and Ab(42); an in vitro capability of mCRP to induce Tau phosphorylation and stimulate production of other AD-precursors including presenilin enhancer protein-2 and phosphorylated amyloid precursor protein (19,20); and from an immunohistochemical study of a cohort of AD post-mortem cases, a strong co-localization of mCRP with inflammatory markers including CD68 (macrophages), nuclear factor kappa B and interleukin-1-beta (IL-1b) (21). Most recently, Zhang et al (22), proposed a mechanism involving mCRP binding and phosphorylation of CD31 on endothelial cells stimulated neuro-inflammation dependent on apolipoprotein E4 postulating this as a pathway leading to increased risk of AD. There is little doubt now that mCRP has an important role in stimulating brain systemic neuro-inflammation and promoting AD pathobiology, whilst a potential role in other brain or CNS/ PNS disorders; including neuropsychological conditions, where mCRP has been recently highlighted as a possible indicator but this has yet to be researched in detail.…”
Section: Evidence Of the Disease Modifying Behavior Of Mcrpmentioning
confidence: 98%